The record of episodic high-energy sedimentation in the western Oak Ridges Moraine, southern Ontario. - Russell, Hazen Algar John. (University of Ottawa (Canada), 2001)
The 160 km long Oak Ridges Moraine in southern Ontario has been interpreted as an interlobate moraine, a subaerial braidplain-defaic deposit, a subglacially formed ridge, or a polygenetic landform of subglacial and proglacial deposits. Because of these significant differences a detailed sedimentological study is needed in order to provide an improved depositional model. This study of the western 40 km of the moraine in the Humber River watershed challenges the concept that it was deposited from seasonal meltwater discharges, climatic modulated ice-marginal fluctuations or in an interlobate position. Instead it is interpreted to have formed in response to changes in the ice-sheet during deglaciation associated with subglacial ponding, episodic and catastrophic subglacial jokulhlaup discharge and seasonal meltwater discharge. The moraine probably formed as the ice-sheet profile and glacial hydraulic system re-equilibrated to the presence of a thinned ice-sheet and a subglacial lake in the Lake Ontario basin. The Oak Ridges Moraine is interpreted to have been deposited in three discrete stages that record sedimentation from both high-energy and low-energy depositional processes. Stage I consists mostly of massive and diffusely-graded sand that is up to 50 m thick and forms the lowest tunnel channel infill. It was deposited rapidly from hyperconcentrated flows some distance downflow of a hydraulic jump that developed as jokulhlaup flow discharged from tunnel channels into a subglacial lake in the Lake Ontario basin. Low energy basinal sedimentation of Stage II is recorded by the upward increase in thin normally graded fine-sand, silt, and clay laminae forming varves. Stage III is characterized by rapid facies changes associated with subaqueous fan, esker and basinal sedimentation. Proximal fan sediment consists of heterogeneous gravel with sand intraclasts and planar-stratified gravel. Immediately downflow the supercritical to subcritical flow transition is recorded by steep-wailed scours and diffusely-graded infill. Farther downflow the subcritical flow region of the fan is dominated by planar cross-stratified medium sand, climbing medium scale cross-stratified sand and small-scale cross-laminated fine sand. Based on an incomplete verve chronology and general evidence of rapid and voluminous sedimentation it is estimated that the moraine was deposited over a short period of time, maybe as little as 100 years. This study provides an additional demonstration of the value of detailed sedimentological studies to advancing understanding of Laurentide meltwater and deglacial processes.
Keywords: Geology.